Answer:
Step-by-step explanation:
In order to make a specific shade of green paint, a painter mixes 1 1/2 quarts of blue paint. Converting 1.5 quarts to cup,
1 quart = 4 cups
1.5 quarts = 1.5 × 4 = 6 cups
She also used 1/2 gallon of white paint. Converting 0.5 gallons to cup,
0.0625 gallons = 1 cup
0.5 gallons = 0.5/0.0625 = 8 cups
This means that the ratio of cups of blue paint to green paint to white paint is 6: 2 :8
Total ratio = 6 +2 + 8 = 16
To make 100 cups of this shade of green,
Cups of blue paint needed = 6/16 × 100 = 37.5 cups
Cups of green paint needed = 2/16 × 100 = 12.5 cups
Cups of white paint needed = 8/16 × 100 = 50 cups
Let
x--------> <span>the speed of the boat in mph
we know that
</span>going upstream the speed is x-7
<span>going downstream the speed is x+7
</span>
let the distance be d
<span>time to go upstream = d/(x-7) </span>
<span>time to go downstream = d/(x+7)
</span>
time going upstream is 3 times going downstream
so
<span>3d/(x+7) = d/(x-7) </span>
<span>divide by d </span>
<span>3/(x+7) = 1/(x-7) </span>
<span>3x-21 = x+7 </span>
<span>2x = 28 </span>
<span>x = 14
</span>
the answer is
<span>the speed of the boat in still water is 14 mph</span>
<h3>
Answer: x = 7 and y = 3</h3>
=====================================================
Explanation:
Apply the difference of squares rule
x² - 4y² = 13
x² - (2y)² = 13
(x - 2y)(x + 2y) = 13
Since x and y are positive integers, this means x-2y and x+2y are both integers as well.
The value 13 is prime. Its only factors are 1 and 13
Since the above equation shows 13 factoring into x-2y and x+2y, then we have two cases:
- A) x-2y = 1 and x+2y = 13
- B) x-2y = 13 and x+2y = 1
----------------
Let's consider case A
We have this system of equations
Add the equations straight down
- x+x becomes 2x
- -2y+2y becomes 0y = 0 which goes away
- 1+13 becomes 14
Therefore we have 2x = 14 solve to x = 7
From here, plug this into either equation to solve for y
x-2y = 1
7 - 2y = 1
-2y = 1-7
-2y = -6
y = -6/(-2)
y = 3
You should get the same result if you used x+2y = 13
----------------
Since we've found that x = 7 and y = 3, notice how case B is not possible
Example: x-2y = 13 becomes 7-2(3) = 13 which is false.
Also, x+2y = 1 would turn into 7+2(3) = 1 which is also false.
-----------------
Let's check those x and y values in the original equation
x² - 4y² = 13
7² - 4*(3)² = 13
49 - 4(9) = 13
49 - 36 = 13
13 = 13
The answer is confirmed.